Ovulation induction in anovulatory infertility is obsolete. Issue 2 (February 2023) - Lawrenz, Barbara; Melado, Laura; Fatemi, Human M.
Abstract: Women with polycystic ovary syndrome make up the vast majority of patients with anovulatory infertility. The commonly accepted treatment guidelines recommend ovulation induction for timed intercourse as the first-line treatment. After a 2-year treatment period, the cumulative pregnancy rates with a singleton live-born baby reached 71% and 78% in two prospective studies. Despite aiming for monofollicular growth, multifollicular responses with subsequent multiple/higher order multiple pregnancies are a dreaded risk associated with ovarian induction. However, the lengthy treatment, the increase of maternal age and the psychological effects of 'obligatory intercourse' are also factors challenging the concept of ovarian induction as the first treatment approach in anovulatory infertility. Nowadays, individualized IVF treatment with cycle segmentation, freeze-all strategies and single-embryo transfers in frozen embryo transfer cycles dramatically reduces the risk of multiple pregnancies, and a cumulative pregnancy rate of 83% can be achieved over three complete cycles, thereby reducing exposure to fertility medication and time to pregnancy. Although on first sight ovarian induction might present the easier and less costly approach, efficient and individualized IVF treatments with low complication rates and the chance of preventing multiple pregnancies challenge this concept, and it seems that the time has come to abandon ovarian induction in anovulatory infertility.